Pengaruh Brand ambassador, Brand image, dan Harga terhadap Keputusan Pembelian Pada Konsumen Produk Skincare Scarlett Whitening Di Sidoarjo - Afifa Nur Rahma; Vera Firdaus; Dewi Komala Sari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to find out The Influence of Brand ambassador, Brand image, and Price On Purchase Decisions On Skincare Product Consumer Scarlett Whitening In Sidoarjo City. This study used a quantitative approach with descriptive methods as a research method. The study's population is consumers who have used Scarlett Whitening's Skincare. The study involved a sample of 105 respondents selected according to the Slovin formula and using non-probability sampling methods and using incidental sampling techniques. The data used in this study consisted of primary data obtained from the distribution of questionnaires to respondents through Google Forms media. Quantitative data analysis techniques use Partial Least Square (PLS) to analyze data. The PLS method used is SmartPLS. Based on the research results, it was found that Brand ambassador had a positive and significant influence on Scarlett Whitening Sidoarjo's skincare Purchase Decision. Brand image has a positive and significant influence on Scarlett Whitening Sidoarjo's skincare Purchase Decision. Prices have a positive and significant influence on Scarlett Whitening Sidoarjo's skincare Purchase Decision. In addition, in this context, Brand ambassador, Brand image, and Price have proven to have a significant influence on Scarlett Whitening Sidoarjo's skincare Purchase Decision. Keywords: Brand Ambassador, Brand Image, Price, Purchase Decision